COMPARATIVE ANALYSIS OF THE THREE BALL SAMPLES FOR DIFFERENT PHYSICO-MECHANICAL PROPERTIES - Gromova, O. V. (Science and Transport Progress, 2007)
The article considers application of the software ANSYS finite-element analysis method for solving the issues related with structural compatibility of materials put in the basis of a construction – old concrete and repair material – new concrete at various ratios of physico-mechanical properties with the purpose of theoretical substantiation of coupling processes in repair of transport constructions.